2008
DOI: 10.1007/s00534-007-1231-8
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal papillary mucinous neoplasm of the pancreas: clinical characteristics and treatment outcomes of 118 consecutive patients from a single center

Abstract: Function-preserving strategies, based on the clinical status of the patient, are necessary in order to avoid possible severe metabolic complications following extended pancreatectomy in patients with benign IPMN because of the low recurrence rate and good prognosis of this entity, irrespective of margin status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 20 publications
(18 reference statements)
5
61
1
Order By: Relevance
“…9 Some reports have described that total pancreatectomy should be considered for patients with main duct IPMNs involving the entire pancreas when the patient's condition permits. [10][11][12] Recently, there have been increasing reports of successful laparoscopic pancreatectomies, however, laparoscopic total pancreatectomies have rarely been described in the literature. 3,13,14 Casadei et al 14 reported a laparoscopically-assisted total pancreatectomy which consisted of a totally laparoscopic body-tail mobilization followed by the opening of a right subcostal mini-laparotomy in order to perform a pancreaticoduodenectomy and a reconstructive phase.…”
Section: Discussionmentioning
confidence: 99%
“…9 Some reports have described that total pancreatectomy should be considered for patients with main duct IPMNs involving the entire pancreas when the patient's condition permits. [10][11][12] Recently, there have been increasing reports of successful laparoscopic pancreatectomies, however, laparoscopic total pancreatectomies have rarely been described in the literature. 3,13,14 Casadei et al 14 reported a laparoscopically-assisted total pancreatectomy which consisted of a totally laparoscopic body-tail mobilization followed by the opening of a right subcostal mini-laparotomy in order to perform a pancreaticoduodenectomy and a reconstructive phase.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,[10][11][12][13] The prognosis after resection of invasive IPMN is reported to be better than that after resection of pancreatic ductal adenocarcinoma. 10,13 According to the Classifi cation of Pancreatic Carcinoma by The Japan Pancreas Society, IPMNs with an invasive carcinoma component can be categorized into tumors with minimally invasive carcinoma (minimally invasive IPMNs) and those with invasive carcinoma originating from an intraductal tumor (invasive IPMNs). 14 Although the defi nition of minimally invasive IPMNs has not been established as yet, these tumors have a similar prognosis to noninvasive IPMNs after surgical resection.…”
Section: Introductionmentioning
confidence: 98%
“…[5][6][7][8]10 Complete resection of noninvasive IPMNs, being CIS or earlier disease, can achieve excellent outcomes. 6,[10][11][12][13] On the other hand the outcome after resection of invasive IPMNs, being tumors with an invasive carcinoma component, is much worse. 4,6,[10][11][12][13] The prognosis after resection of invasive IPMN is reported to be better than that after resection of pancreatic ductal adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A borderline malignant tumor can progress to an overt malignant tumor, but long-term survival is expected after adequate surgical resection of the tumors compared with usual pancreatic cancer [2][3][4][5]. Therefore, surgeons need to consider the patients' quality of life when managing patients with IPMT involving the entire pancreas, and organ-preserving pancreatectomy may be appropriate for them.…”
mentioning
confidence: 98%